POLA KOMUNIKASI SEKUNDER MAHASISWA IAIN PALOPO DALAM PERSPEKTIF ETIKA KOMUNIKASI ISLAM - Risaldi Alfauzie; Masmuddin Masmuddin; Subekti Masri (An-Nida : Jurnal Komunikasi Islam, 2024)
The aim of this research is to understand the secondary communication patterns of IAIN Palopo students, to analyze the relationship between the principles of Islamic communication ethics and the secondary communication patterns of IAIN Palopo students, and to analyze the application of Islamic communication ethics in the secondary communication patterns of IAIN Palopo students. The type of research used is descriptive qualitative with an interpersonal communication approach. In order to obtain data in this research, the author used techniques including observation, interviews and documentation. The results of this research show that (1) the secondary communication patterns of IAIN Palopo students via WhatsApp and Instagram show that social media plays an important role in supporting students' academic and social activities; (2) IAIN Palopo students have implemented several principles of Islamic communication ethics well, but there are still a small number who do not understand and are able to apply the principles of Islamic communication ethics in the process of communicating in the media; and (3) Even though there has been progress in several aspects of implementing Islamic communication ethics, there are still students who have not implemented Islamic communication ethics properly when communicating in the media with other students and lecturers so that communication in the media is still not running well.